2012
DOI: 10.1073/pnas.1201724109
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulated viscous channel in the nuclear pore complex

Abstract: The nuclear pore complex (NPC), the sole gateway for nucleocytoplasmic exchange in eukaryotic cells, allows for the passive diffusion of small molecules and transport-receptor-facilitated translocation of signal-dependent cargo molecules. Whether small molecules passively diffuse through a single central channel or through multiple holes of a hydrogel network is a subject of debate. Additionally, whether the passive and facilitated transport systems occupy distinct or overlapping physical regions of the NPC re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
238
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(272 citation statements)
references
References 31 publications
(67 reference statements)
32
238
2
Order By: Relevance
“…3). 79,82 Recently, the distribution of single-molecule locations along the θ dimension in each NPC was experimentally confirmed to be approximately homogenous.…”
Section: D Mapping Of Nucleocytoplasmic Transport Via Speed Microscopymentioning
confidence: 99%
See 3 more Smart Citations
“…3). 79,82 Recently, the distribution of single-molecule locations along the θ dimension in each NPC was experimentally confirmed to be approximately homogenous.…”
Section: D Mapping Of Nucleocytoplasmic Transport Via Speed Microscopymentioning
confidence: 99%
“…To meet the above requirements for the mapping of nuclear transport, an innovative imaging approach that combines single-particle tracking and a deconvolution algorithm has recently been developed in our laboratory. [79][80][81][82] not the θ coordinate. The distribution of single-molecule locations along the θ dimension is then averaged to make it uniform, and thus, θ becomes a constant for each single-molecule location, as (r, x, constant).…”
Section: D Mapping Of Nucleocytoplasmic Transport Via Speed Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Are there protein spurs (side-chains or, at greater reach, N-or C-termini) that emanate inward acting as a rheological barrier or are they active players (i.e., transport as a "spaghetti opera")? This remains a controversial aspect of the nuclear export field, and a recent study has suggested a very different biophysical structure of the NPC central channel (15). Single-particle tracking could play a role in the further resolution of this issue, combined with the appropriate experimental variables.…”
mentioning
confidence: 99%